Chemical variability of phenolic compounds in Phyllanthus niruri - Albrecht, Ingrid [UNESP]; Da Silva, Natália Coelho [UNESP]; Carvalho, Flávio Alexandre [UNESP]; Oda, Fernando Bombarda [UNESP]; Dos Santos, André Gonzaga [UNESP] (Ecletica Quimica, 2023)
Phyllanthus niruri L. has been used in folk medicine to treat hepatitis, diabetes, urinary tract disorders, and renal calculi. Here, the chemical differences among its organs and the seasonal chemical variability in the aerial parts were evaluated. The chromatographic profile and gallic acid, corilagin, and ellagic acid contents were determined by ultrahigh performance liquid chromatography with photodiode array ultraviolet (UHPLC-PDA/UV) method, which showed adequate resolution and a short analysis time. The contents of gallic acid, corilagin and ellagic acid in the leaf extract were 2.8, 6.7 and 7.9%, respectively, whilst their contents in the stem and root extracts were lower (< 0.2%). Thus, using the whole plant or aerial parts for herbal medicines can produce different biological responses. The chemical profile of the aerial parts showed only quantitative variation over 12 months. The seasonal content of gallic acid showed no correlation with monthly rainfall, but the contents of corilagin and ellagic acid were positively correlated with rainfall.